2013
DOI: 10.1590/0001-37652013112412
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of stem bleeding disease in coconut palm in the state of sergipe, Brazil

Abstract: Stem bleeding disease (resinosis) of coconut palm is caused by Thielaviopsis paradoxa and is very important in the state of Sergipe, Brazil. Understanding the epidemiological behavior of the disease is essential for establishing more efficient control strategies. Thus, we characterized the temporal progression and spatial distribution of stem bleeding in a commercial orchard under conditions of natural infection in the area of Neopolis, Sergipe. Three plots with 729 plants each were selected and evaluated ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Additionally, the degree of aggregation according to both methods, D and I a , increased over time, showing higher values in the last assessments. Initial infections of stem bleeding disease of coconut palm had a random pattern in the first assessments but evolved to an aggregated pattern in the last [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the degree of aggregation according to both methods, D and I a , increased over time, showing higher values in the last assessments. Initial infections of stem bleeding disease of coconut palm had a random pattern in the first assessments but evolved to an aggregated pattern in the last [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…They verified that the plant height and root length of the plants cultured in vitro were significantly smaller in the first one to two years, but there was no significant difference after more than five years (Koffi et al, 2013). Carvalho et al described the spatial distribution of natural infection of coconut resin deposition disease in commercially available orchards and its progression over time (Carvalho et al, 2013). Thomas et al proposed an automatic coconut quality rating method based on sound processing technology, which mainly judges whether the coconut has sufficient water content or is damaged and rotted (Thomas and Anita, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al. described the spatial distribution of natural infection of coconut resin deposition disease in commercially available orchards and its progression over time ( Carvalho et al., 2013 ). Thomas et al.…”
Section: Introductionmentioning
confidence: 99%
“…The ascomycete C. paradoxa not only infects palm trees, such as Cocos nucifera , Phoenix dactylifera , Borassus flabellifer , Butia capitata , Elaeis guineensis , and Areca catechu , but also infects other plants, including Ananas comosus , Mangifera indica , Musa paradisiaca , Solanum muricatum , Theobroma cacao , and Zea mays , resulting in large agricultural losses [3]. The biological characteristics of the pathogen have thus far been described [5], and the partial and temporal dynamics of stem-bleeding have been recorded for clarifying the disease progression and characterizing the production losses from the disease [6]. In addition, some CSB disease management studies have been reported, including physical, chemical, and biological control measures [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%